Relationship among LRP1 expression, Pyk2 phosphorylation and MMP‐9 activation in left ventricular remodelling after myocardial infarction. Issue 9 (4th April 2017) - Revuelta‐López, Elena; Soler‐Botija, Carol; Nasarre, Laura; Benitez‐Amaro, Aleyda; de Gonzalo‐Calvo, David; Bayes‐Genis, Antoni; Llorente‐Cortés, Vicenta
Abstract: Left ventricular (LV) remodelling after myocardial infarction (MI) is a crucial determinant of the clinical course of heart failure. Matrix metalloproteinase (MMP) activation is strongly associated with LV remodelling after MI. Elucidation of plasma membrane receptors related to the activation of specific MMPs is fundamental for treating adverse cardiac remodelling after MI. The aim of current investigation was to explore the potential association between the low‐density lipoprotein receptor‐related protein 1 (LRP1) and MMP‐9 and MMP‐2 spatiotemporal expression after MI. Real‐time PCR and Western blot analyses showed that LRP1 mRNA and protein expression levels, respectively, were significantly increased in peri‐infarct and infarct zones at 10 and 21 days after MI. Confocal microscopy demonstrated high colocalization between LRP1 and the fibroblast marker vimentin, indicating that LRP1 is mostly expressed by cardiac fibroblasts in peri‐infarct and infarct areas. LRP1 also colocalized with proline‐rich tyrosine kinase 2 (pPyk2) and MMP‐9 in cardiac fibroblasts in ischaemic areas at 10 and 21 days after MI. Cell culture experiments revealed that hypoxia increases LRP1, pPyk2 protein levels and MMP‐9 activity in fibroblasts, without significant changes in MMP‐2 activity. MMP‐9 activation by hypoxia requires LRP1 and Pyk2 phosphorylation in fibroblasts. Collectively, our in vivo and in vitro data support a major role of cardiac fibroblast LRP1 levels on MMP‐9 up‐regulation associated with ventricular remodelling after MI.